مستوى الطموح الأكاديمي و علاقته بالتوافق الدراسي لدى الطالبات المتزوجات بجامعة عمار ثليجي - حليمي خضرة; رزيقات منال; عياط لمين (My University, 2019)
The current study aims to know the level of academic ambition and its relation to the academic compatibility of a sample of female students married at Ammar Thalami University in Laghouat, as well as to find out the relationship between academic compatibility and academic ambition according to the students who have children who do not have children and to achieve the research purposes, The study sample of 40 married students studied or are currently studying at the Ammar Thaliji Laghouat University and have chosen twenty students with twenty children and twenty students who have no children. The level of ambition, Data were unloaded and processed using SPSS 20 and the following statistical methods were used: - percentage -Mathematical averages -standard deviations Pearson correlation coefficient The following results were obtained: First, there is a high level of academic ambition in a sample of female students married to Ammar Thaliji University Second: The existence of a high level of academic compatibility in a sample of students married to Ammar Thaliji University Thirdly, there is no relationship between the level of academic ambition and academic compatibility Fourth: There are no differences in the level of academic ambition of married students who have children and those who have no children Fifth: There are no differences in the level of academic compatibility of married students who have children and those who have no children